The role of ECMO in neonatal and paediatric patients. Issue 5 (May 2019) - Robinson, Simon; Peek, Giles
Abstract: ECMO or extracorporeal membrane oxygenation has now been part of healthcare for over 40 years. During that time, changes in circuit technology have resulted in improved survival and have facilitated the use of ECMO in more challenging patient groups in whom ECMO was previously considered to be contraindicated. Further advances have allowed ECMO to progress out of the specialist centres and nearer to patients, in the form of mobile ECMO. Patient selection remains key to a successful outcome since ECMO is a supportive therapy utilised whilst waiting for a reversible condition to resolve through other treatment strategies.